Kekuatan Hukum GRONDKAART dan Problematikanya di Indonesia - Pahlevi, Farida Sekti (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Land tenure and use according to land law in Indonesia must be based on Land Rights. Land rights will give authority to the right holder to control and use the land. Grondkaart is proof of land ownership owned by PT. KAI in order to be able to control and take over assets for the benefit of railway operations. However, the legal power of Grondkaart as evidence of land rights is still in dispute. With a normative juridical analysis, this paper discusses the legal force of PT. KAI's Grondkaart, its problems in Indonesia, and the legal solution for saving PT KAI's assets. The results of this study are: First, Grondkaart can be used as proof of ownership of rights to PT.KAI's assets, but PT.KAI is obliged to register Grondkaart's land to the National Land Agency as Management Rights and/or Use Rights in order to have a strong legal standing. Second, in order to save PT KAI's Grondkaart land, in addition to being obliged to carry out land registration, it must also examine the historical history of the land, establish synergies, synchronization, and cooperation with stakeholders, and prioritize mediation and deliberation when disputes arise